2011
DOI: 10.1111/j.1600-0412.2011.01271.x
|View full text |Cite
|
Sign up to set email alerts
|

First trimester prediction of small‐ and large‐for‐gestation neonates by an integrated model incorporating ultrasound parameters, biochemical indices and maternal characteristics

Abstract: Prediction for birthweight deviations is feasible using data available at the routine 11-14 weeks' examination. Delta CRL and delta nuchal translucency were significant independent predictors for both SGA and LGA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
54
0
2

Year Published

2012
2012
2018
2018

Publication Types

Select...
8

Relationship

7
1

Authors

Journals

citations
Cited by 48 publications
(60 citation statements)
references
References 33 publications
4
54
0
2
Order By: Relevance
“…Variance inflation factor for co-linearity assessment and White's test for heteroscedasticity were used. We adjusted first trimester ultrasound parameters for CRL according to previous published first trimester nomogramms [27]. Thus we converted NT and FHR to d-NT and d-FHR respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Variance inflation factor for co-linearity assessment and White's test for heteroscedasticity were used. We adjusted first trimester ultrasound parameters for CRL according to previous published first trimester nomogramms [27]. Thus we converted NT and FHR to d-NT and d-FHR respectively.…”
Section: Discussionmentioning
confidence: 99%
“…The fact that FV captures more efficiently fetal growth in the first trimester could be important as recent studies support a potential link between early fetal growth deviations, assessed by CRL, with pregnancy complications, such as preterm birth, low birth weight, or small for gestational age [5,13,14]. We have previously reported that birth weight deviations are predictable by using an integrated model incorporating the delta-CRL value and ultrasound parameters, biochemical indices, and maternal characteristics [14].…”
Section: Discussionmentioning
confidence: 95%
“…The same analysis was repeated for mean Ut-PI. We used previous published formulas to calculate delta values for nuchal translucency (d-NT) and fetal heart rate (d-FHR) [14,25]. Delta values were computed by subtracting the expected value from the observed.…”
Section: Discussionmentioning
confidence: 99%
“…Sin embargo, en fetos macrosómicos, la TN en el primer trimestre era mayor que en fetos con peso adecuado para la edad gestacional [71][72][73]75,76 .…”
Section: Marcadores Biofísicosunclassified
“…Los modelos de predicción de macrosomía incluyen factores de la historia clínica materna, como edad, peso, talla, raza, antecedente de feto macrosómico, tabaquismo, diabetes mellitus e hipertensión crónica, marcadores biofísicos como la TN y el IP medio de arterias uterinas, y marcadores bioquímicos como la PAPP-A y la b-hCG libre en sangre materna, obteniendo tasas de detección alrededor de un 35 y un 20% para tasas de falsos positivos del 10 y el 5%, respectivamente 33,[71][72][73]76 .…”
Section: Modelos De Predicciónunclassified